THERAPEUTIC LIGHT EFFECTUATING PHYSIOLOGICAL RESPONSES - BURSTEIN, Rami; MAXIK, Fredric (2023)
A system for selective emission of therapeutic monochromatic light including a light source operable to emit light within a monochromatic wavelength range, defining a therapeutic light, the monochromatic wavelength range being associated with a physiological response in a human subject, a non-transitory computer-readable storage medium, and a controller positioned in communication with each of the non-transitory computer-readable medium and the light source and operable to receive an indication of optical characteristics of a space into which the light source is positioned to emit light, defined as a spatial optical characteristic and operate the light source to emit the therapeutic light responsive to the spatial optical characteristic. L'invention concerne un système d'émission sélective de lumière monochromatique thérapeutique comprenant une source de lumière utilisable pour émettre de la lumière dans une plage de longueurs d'onde monochromatique, définissant une lumière thérapeutique, la plage de longueurs d'onde monochromatique étant associée à une réponse physiologique chez un sujet humain, un support de stockage non transitoire lisible par ordinateur et un dispositif de commande positionné en communication avec chacun du support non transitoire lisible par ordinateur et de la source de lumière et utilisable pour recevoir une indication de caractéristiques optiques d'un espace dans lequel la source de lumière est positionnée pour émettre de la lumière, définie comme une caractéristique optique spatiale, et faire fonctionner la source de lumière pour émettre la lumière thérapeutique en réponse à la caractéristique optique spatiale.